2021
DOI: 10.22395/angr.v19n38a2
|View full text |Cite
|
Sign up to set email alerts
|

El rol del eWOM en la comunicación de RSC en redes sociales

Abstract: Las empresas tratan de innovar en sus estrategias de comunicación para ofrecer información tanto sobre sus bienes y servicios, como información corporativa relacionada con las actividades de RSC que la empresa lleva a cabo. En la actualidad, la comunicación sobre RSC es muy importante y poco se sabe acerca de la mejor forma de hacerlo. En este sentido, las redes sociales se han convertido en un importante canal de comunicación entre empresas y consumidores. A través de las redes sociales, los individuos compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
4
0
4
Order By: Relevance
“…India is betting on technological development, as well as CSR as tools for change and the sustainable development of the country. This fact confirms the importance of social media, in this case, Twitter, as a tool for the communication of CSR (Rodríguez & Chalmeta, 2020;Zhang et al, 2020;Aguirre et al, 2021). As authors such as Rodríguez and Chalmeta (2020) had claimed, our work has shown how the establishment of CSR communication strategies through social media and being constant in maintaining a daily dialogue with interested groups, can make the message, reaches the entire world, making the organization an influencer in the matter of CSR, which will give it credibility and trust.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…India is betting on technological development, as well as CSR as tools for change and the sustainable development of the country. This fact confirms the importance of social media, in this case, Twitter, as a tool for the communication of CSR (Rodríguez & Chalmeta, 2020;Zhang et al, 2020;Aguirre et al, 2021). As authors such as Rodríguez and Chalmeta (2020) had claimed, our work has shown how the establishment of CSR communication strategies through social media and being constant in maintaining a daily dialogue with interested groups, can make the message, reaches the entire world, making the organization an influencer in the matter of CSR, which will give it credibility and trust.…”
Section: Discussionsupporting
confidence: 58%
“…These results highlight the importance of the social perspective of CSR, in line with Barauskaite and Streimikiene (2020) who point out that there is a social demand towards companies and their participation and contribution to the welfare of society. In this sense, it can be stated that it is essential for companies to understand the needs of society over time so that their discourses are in line with their interests (Aguirre et al, 2021) and thus achieve the interactivity and dialogue necessary to ensure effective communication (Rodríguez & Chalmeta, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations